Do Middle-Income Countries Continue to Have the Ability to Deal with the Global Financial Crisis? - van Doorn, Ralph; Suri, Vivek; Gooptu, Sudarshan (2012)
This paper introduces an "index of macroeconomic space" -- demonstrating the ability of a country to run a countercyclical fiscal policy or a fiscal stimulus at any point in time -- to show how a sample of 20 mostly middle-income countries had entered the 2008 global financial crisis with different initial conditions that, in turn, determined their ability to respond to this crisis. Since 2008, many have implemented expansionary fiscal policies and have used up available macroeconomic space. Most have had to resort to increased borrowing by the public sector, both externally and domestically. Can the middle-income countries restore their pre-2008 macroeconomic space (to the level given by historical averages of key macroeconomic variables) or contain it from further deterioration in the medium term? In an endeavor to address this question, this paper shows, through illustrative scenarios, that the room to maneuver for some countries is somewhat limited unless they embark on severe, unprecedented fiscal adjustments or they may need more time to do so than current projections seem to suggest.